2022
DOI: 10.3390/ijerph19095073
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Classes in the Context of Prenatal Anxiety and Depression during the COVID-19 Pandemic

Abstract: Perinatal maternal anxiety and depression negatively affect intrauterine fetal development, birth outcome, breastfeeding initiation, duration, and milk composition. Antenatal classes potentially reduce the anxiety of pregnant women and may thus contribute to healthy infant development. The study investigates the relationship between participation in online or in-person antenatal classes and levels of anxiety and depression in Polish women during the COVID-19 pandemic. The study group included 1774 adult, non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…Women who attended face-to-face antenatal education experienced a statistically significant difference in lowered levels of anxiety, in comparison to women undertaking online education, or those who did not attend classes (Ciochan et al, 2022). Ciochan et al (2022) suggested this may be associated with the additional element of social interaction, the participant's willingness to engage online and how this positively influenced well-being. The reported use of digital resources seemed reflective of the individual's comfort utilizing technology (Arcia et al, 2019).…”
Section: Limited Generalizability Due To Potential Self-selection Bia...mentioning
confidence: 99%
See 3 more Smart Citations
“…Women who attended face-to-face antenatal education experienced a statistically significant difference in lowered levels of anxiety, in comparison to women undertaking online education, or those who did not attend classes (Ciochan et al, 2022). Ciochan et al (2022) suggested this may be associated with the additional element of social interaction, the participant's willingness to engage online and how this positively influenced well-being. The reported use of digital resources seemed reflective of the individual's comfort utilizing technology (Arcia et al, 2019).…”
Section: Limited Generalizability Due To Potential Self-selection Bia...mentioning
confidence: 99%
“…In traditional face-to-face antenatal education, women highly regard the sharing of information and networking that occurs, whereas online antenatal education may limit opportunities to strengthen social supports and connection, especially at a local community level (Arcia et al, 2019;Ciochan et al, 2022;Kovala et al, 2016).…”
Section: Limited Generalizability Due To Potential Self-selection Bia...mentioning
confidence: 99%
See 2 more Smart Citations
“…Kelas ibu hamil dan posyandu juga bertujuan untuk mentransfer pengetahuan praktis tentang persalinan, nifas, menyusui dan kebutuhan bayi serta balita. Selain peran pendidikan, kelas antenatal juga memenuhi peran psikososial yang penting karena kemungkinan terjadi pertukaran informasi dan pengalaman antara orang tua di bawah bimbingan seorang bidan untuk memberikan dukungan kepada calon ibu dan membantunya mengatasi perubahan dan kebutuhan yang diinginkan oleh ibu hamil (Ciochoń et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified